GAYA PERFORMATIF DALAM FEATURE “KAPAN KE JOGJA LAGI?” - Novanda Fibrianti (Saraswati)
Television is the most effective one way communication media to deliver a message. A television is not only a communication tool, but also as an entertainment, education, and information‘s media. In this case, much of television station offering an interest program for the audiences, but not all of the programs has an education value.The creation of program ―Kapan Ke Jogja Lagi?‖ have a purpose to give an alternative choices‘s program for audiences which have an education value, information, and entertainment. This program is not only offering a narative concept but also an interesting visual concept at the same time.The object creation of this artwork is Dagadu, by taking it‘s style and characteristic, which in a design‘s context, have a pop art and modern style and use ‗plesetan ‘ language at the same time, this object then, packaged on a feature form. The aesthetic‘s concept of this artwork creation is performative style, that delivered with videography technic, editing, artistic layout, and script.Keywords: Feature, Dagadu, Pop art, Plesetan , Performative